Design of Efficient Type‐II ZnGeN2/In0.16Ga0.84N Quantum Well‐Based Red LEDs. Issue 8 (30th April 2019) - Hyot, Bérangère; Rollès, Mélanie; Miska, Patrice
Abstract : While GaN‐based blue and green LEDs are commercially available, research for efficient red LED based on GaN is still ongoing. These developments are crucial for monolithic integration of RGB colors and the development of nitride‐based full‐color high‐resolution displays. In this perspective, a new red LED architecture based on type‐II ZnGeN2 /InGaN quantum well (QW) has been reported. Due to high valence band offset in the type‐II structure, the strong confinement of holes in the ZnGeN2 layer allows the use of a lower In‐content InGaN QW to extend the emission into the red wavelength regions, in comparison to the traditional InGaN QWs with uniform In content. The red region can be reached with only 16% of In with suitable width and position of the ZnGeN2 layer in the InGaN QW. Simulation studies promise a significant enhancement of the spontaneous emission and the possibility to reach both a better external quantum efficiency (EQE close to 60%) and light output when using the type‐II structure, in comparison to the conventional InGaN QW emitting at the same wavelength. Abstract : New LED architectures based on a type‐II ZnGeN2 /InGaN quantum well enable to reach the red wavelengths with only 16% of In. The authors' designs reveal a significant enhancement of the electron–hole wavefunctions overlap and consequently an increased radiative recombination rate compared to the classical In‐rich (35% In) InGaN quantum wells needed to reach the red emission.